МОЖЛИВОСТІ ВИКОРИСТАННЯ ІГРОВОГО НАВЧАННЯ ЯК ПРОЦЕСУ ПІДВИЩЕННЯ ДІАЛОГІЧНОГО СПІЛКУВАННЯ МАЙБУТНІХ ПЕДАГОГІВ (Педагогіка вищої та середньої школи, 2022)
The article deals with the various problems and aspects of  communicational culture formftijn in dialog training studying situation of professional oriention.